AL-USLUBIYYAH DALAM TRADISI LINGUISTIK ARAB: PERSPEKTIF TEORITIS DAN HISTORIS - Hamzah Fathurrohman; Ahmad Sururi; Rizzaldy Satria Wiwaha (STKIP Subang, 2026)
Language functions not only as a means of communication but also as a medium of expression that embodies aesthetic and rhetorical values. In linguistic studies, variations in language use related to modes of expression are examined within the field of stylistics, which in the Arabic linguistic tradition is known as al-uslubiyyah. This study aims to explore the theoretical concept of al-uslubiyyah, the stylistic elements within the Arabic linguistic tradition, its historical development, and its role in the analysis of the Arabic language. The research employs a qualitative method with a library research approach. The findings reveal that al-uslubiyyah is a field of study that analyzes language style through various linguistic dimensions, including phonological, morphological, syntactic, semantic, and rhetorical aspects, while also taking into account the context of communication in language use. Furthermore, the development of al-uslubiyyah demonstrates a continuity between the classical tradition of balaghah (Arabic rhetoric) and modern linguistic approaches. Stylistic studies also play a significant role in understanding the characteristics of language style in literary works, religious texts, and academic discourse in Arabic. Based on these findings, it can be concluded that al-uslubiyyah constitutes a comprehensive approach to Arabic language analysis, as it integrates linguistic, aesthetic, and communicative dimensions, thereby contributing significantly to a deeper understanding of the meaning, function, and beauty of the Arabic language.